If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6+3q+2=2q-9
We move all terms to the left:
-6+3q+2-(2q-9)=0
We add all the numbers together, and all the variables
3q-(2q-9)-4=0
We get rid of parentheses
3q-2q+9-4=0
We add all the numbers together, and all the variables
q+5=0
We move all terms containing q to the left, all other terms to the right
q=-5
| x/4+18=15 | | 8/3=y/19-y | | x/1=8 | | 7-6z=-6z+7 | | 3x+4+8x=15 | | 2(p+7)=18 | | 4x-4=4x-1 | | (x+7)+(7x-3)+3x=180 | | 8h+8=-8h+8 | | X-4*2=3x+10-x | | (2x-15)=(x+45) | | -4n+32=9+8n | | 14=6+–4c | | 3(50+75)=x | | 3.8=2p+3 | | 75⋅7x=7^15 | | 7-8k=-8k+7 | | -6(8f+9)=-8(7f+8)+6f | | -5x-24=-6(4+2x) | | -4(x-5)+2x=x-1 | | -16=a/2-7 | | h+-826=-186 | | 3x+5+6x-4=3x+11+ | | -7u+8=-9u-6 | | 4(-2y–3)=12 | | h+128=133 | | k-139=92 | | -3+8=-2+2x | | 2x+16=-8-10x | | 2.4=6-p | | 1-4w=1+8w | | 300+3x=500+x |